Dose Analysis of Organs at Risk of Breast Cancer Patients with IMRT and 3D-CRT Techniques Based On Dose Volume Histogram (DVH) (International Journal of Scientific Research in Science and Technology, 2025)
Breast cancer therapy can be performed using Three-Dimensional Conformal Radiotherapy (3D-CRT) and Intensity Modulated Radiation Therapy (IMRT) techniques. This study aims to compare the effectiveness of IMRT and 3D-CRT techniques in terms of radiation gain, conformality, and homogeneity. The Dose Volume Histogram (DVH) of both techniques collected from 10 breast cancer patients was analyzed. Conformity Index (CI) and Homogeneity Index (HI) on planning target volume (PTV), as well as dose to organs at risk (OAR) according to Quantitative Analysis of Tissue Effect in the Clinic (QUANTEC) rules were evaluated. The results showed that none of the patients received the optimal dose at PTV using the 3D-CRT technique, while all patients received the optimal dose at PTV using the IMRT technique. For radiation dose to the OAR of the lung, all patients received minimal dose with both techniques according to QUANTEC. The IMRT technique had a 10% incidence of pneumonitis toxicity, while the 3D-CRT technique showed that 3 patients had more than 10%, 5 patients more than 20%, and 2 patients more than 30% risk of pneumonitis. For cardiac OAR, all patients with both techniques met the QUANTEC rule with less than 15% risk of pericarditis. The 3D-CRT technique had a CI value on PTV of (0.7504 ± 0.0675) and HI of (0.3250 ± 0.0479), while the IMRT technique had a CI value of (0.9783 ± 0.0088) and HI of (0.1161 ± 0.0089). The results of this study indicate that the IMRT technique is more optimal in terms of radiation gain, conformity, and homogeneity compared to the 3D-CRT technique in the context of radiation therapy for breast cancer patients.